A REVIEW ON ALZHEIMERS DISEASE AND ITS CONCEPTS IN AYURVEDA - Aditya Shahaji, *Favade; Sadhana P, Chavan (International Journal of Ayurveda and Pharma Research, 2015)
Alzheimers disease is the form of dementia and usually occur in the old age. In Alzheimers disease death of brain cells leads to memory loss. Modern science says AÎ² (amyloid beta) is causative agent of Alzheimers disease and also some infections, toxins and metabolic disorders. The cholinergic deficiency in this disease is responsible for most of the short term memory which leads to progressive loss of memory, deterioration of all intellectual functions, increases apathy, decreases speech function, disorientation and gait irregularities. Modern science have explained symptomatic treatment which may lead to adverse effects. Ayurveda has explained Alzheimers disease under Vatavyadhi which may be cause due to imbalance of Vatadosha. Ayurveda has mentioned some herbs which are said as tonics for nervous system and memory enhancers which not only act on brain cells but whole nervous system. Exact mechanism of these drugs is not clear but some of them have valuable compounds that show their roles on pharmacological activities. Yoga and meditation is most helpful in disorders related to nervous system. According to research patients who performed meditation and yoga those had less atrophy in parts of the brain. This review article helps to know about Alzheimers disease in modern and Ayurvedic view and some individual herbs and some new things which play a very crucial role in Alzheimers disease.